2017
DOI: 10.2903/j.efsa.2017.4691
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into experimental toxicological properties of plant protection products having a potential link to Parkinson's disease and childhood leukaemia†

Abstract: In 2013, EFSA published a literature review on epidemiological studies linking exposure to pesticides and human health outcome. As a follow up, the EFSA Panel on Plant Protection Products and their residues (PPR Panel) was requested to investigate the plausible involvement of pesticide exposure as a risk factor for Parkinson's disease (PD) and childhood leukaemia (CHL). A systematic literature review on PD and CHL and mode of actions for pesticides was published by EFSA in 2016 and used as background documenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 510 publications
(923 reference statements)
0
29
0
Order By: Relevance
“…Strong associations were found and two relevant qualitative AOPs were developed. The PPR panel concluded that AOP-informed Integrated Approaches to Testing and Assessment (IATA) for parkinsonian motor symptoms can also be used to investigate such effects for binary mixtures of pesticides (EFSA PPR Panel, 2017) An important consideration in applying component-based approaches is whether and how to account for potential interactions between components. Interactions are defined as joint action between multiple chemicals that differ from dose addition or response addition categorised as less than additive (antagonism, inhibition, masking) or greater than additive' and are additive (synergism, potentiation).…”
Section: Risk Assessment Approachesmentioning
confidence: 99%
“…Strong associations were found and two relevant qualitative AOPs were developed. The PPR panel concluded that AOP-informed Integrated Approaches to Testing and Assessment (IATA) for parkinsonian motor symptoms can also be used to investigate such effects for binary mixtures of pesticides (EFSA PPR Panel, 2017) An important consideration in applying component-based approaches is whether and how to account for potential interactions between components. Interactions are defined as joint action between multiple chemicals that differ from dose addition or response addition categorised as less than additive (antagonism, inhibition, masking) or greater than additive' and are additive (synergism, potentiation).…”
Section: Risk Assessment Approachesmentioning
confidence: 99%
“…It was also noted that chlorpyrifos can produce DNA damage through topoisomerase II inhibition, as reported in one study using human foetal liver haematopoietic stem cells (Lu et al., ), which was mentioned in the EFSA Scientific Opinion on the ‘Investigation into experimental toxicological properties of plant protection products having a potential link to Parkinson's disease and childhood leukaemia’ (EFSA PPR Panel, ), but not evaluated in the RAR. Topoisomerase II inhibition is a mechanism likely to have a threshold (EFSA Scientific Committee, ); in addition, topoisomerase II inhibition may be involved as a molecular initiating event (MIE) for infant leukaemia (EFSA PPR Panel, ). All the experts agreed that a new Comet assay study might not be able to cover this concern.…”
Section: Assessmentmentioning
confidence: 99%
“…Some experts also pointed out that epidemiological studies showed an important association between pesticides exposure and childhood leukaemia, including infant leukaemia (Ntzani et al., ; Hernández and Menéndez, ). It was noted that it is not possible to measure endpoints relevant for childhood leukaemia in current OECD standard Test Guidelines, due to higher sensitivity of haematopoietic stem and progenitor cells (HSPCs) compared to the standard cells, and the lack of exposure during the critical period (EFSA PPR Panel, ). This could be covered (in terms of exposure window, developmental period) by the extended one generation OECD 443 Test Guideline study (OECD, ), but the study is not designed for carcinogenicity assessment.…”
Section: Assessmentmentioning
confidence: 99%
“…Rotenone and MPP + , for which comprehensive studies were available, including mechanistic research and human data, have been used as main examples for AOP:3. On this basis, mechanistic plausibility could be demonstrated for epidemiological observations (Ockleford et al 2017). Notably, the AOP:3 has particular features on both ends: i) the binding of known inhibitors to cI (MIE) always leads to inhibition of the complex (Sherer et al 2007;Troger et al 2020).…”
Section: Introductionmentioning
confidence: 96%